1989
DOI: 10.1088/0954-3899/15/7/010
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the capture reaction H(n, d)γ at 25.6 MeV

Abstract: The neutron-proton capture reaction has been measured at E, = 25.6 MeV.From the data the total and the differential cross section at 0" were determined. The results are compared with photodisintegration data and theoretical calculations and found to be in agreement with both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
(6 reference statements)
1
4
0
Order By: Relevance
“…[27], diagonal crosses; Ref. [28], open circles; our previous work [35], double circles; the present work (preliminary). The solid curve and the dashed curve stand for the ENDF/B-VII evaluation [23] and the calculation with the momentum-space approach [24], respectively.…”
Section: Results the D(γp)n Reaction Cross Sectionsupporting
confidence: 51%
“…[27], diagonal crosses; Ref. [28], open circles; our previous work [35], double circles; the present work (preliminary). The solid curve and the dashed curve stand for the ENDF/B-VII evaluation [23] and the calculation with the momentum-space approach [24], respectively.…”
Section: Results the D(γp)n Reaction Cross Sectionsupporting
confidence: 51%
“…In E. coli it was suggested that the PG to DPG conversion plays a vital role in cell growth [21]. The molecular basis for such a role is yet /ml of each) and either [1-"kloleate or [l-'4C]palmitate.…”
Section: The Effect Of 7p-oh Cholesterol On the Chemical Composition mentioning
confidence: 99%
“…A balanced review of all data in the relevant energy range has been given in Refs. [2] and [8], while the general status of the theoretical as well as the experimental situation for the deuteron photodisintegration is extensively described in a recent review by Arenhovel and Sanzone [10].…”
mentioning
confidence: 99%
“…Traditionally, this (y,p) cross section (in the c.m. system) is written in terms of the Partovi [11]expansion: (8) =a +b sin 8+c cos8 de 45 1992 The American Physical Society 861 energy region, even more so as its magnitude only represents 2 -7% of the 90' differential cross section.…”
mentioning
confidence: 99%